The contribution of empowered women programs in promoting gender equality for sustainable development goals - Tazkianida, Radhina Fasya (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: The low representation of women at the village level has prompted various demands for women to be given space for participation. Wahid Foundation is one of the organizations focused on women's issues, which led the researcher to choose the title The Contribution of Wahid Foundation in the Empowered Women Program Toward Gender Equality in Durenseribu Village, Depok. Methods: This research employed a qualitative method with a descriptive approach, utilizing observation, interviews, and document analysis. The interviews were conducted with seven respondents, including representatives from the Working Group of Durenseribu Village, youth representatives, women's group representatives, the village government, the regional coordinator for Peaceful Villages in West Java Province, and the Program Officer of Wahid Foundation. Theories applied in this research include the theory of contribution, social service theory, program theory, women's theory, gender equality theory, welfare state theory, and policy theory. Findings: The findings of this research indicate that Wahid Foundation’s contribution through the Empowered Women program towards gender equality in Durenseribu, as a pioneer in achieving one of the Sustainable Development Goals, aligns well with the applied theories. Conclusion: Gender equality within the Empowered Women program in Durenseribu is progressing well, although there are some challenges in the implementation of the program. Novelty/Originality of this article: This study highlights how Wahid Foundation has succeeded in becoming a pioneer in promoting gender equality at the village level through the Empowered Women program, as well as its contribution to achieving the Sustainable Development Goals at the local level.